PENGARUH CAR, NIM, LDR, DAN BOPO TERHADAP ROA PADA PERBANKAN DI BEI - Natasya Rosandy; Thio Lie Sha (Jurnal Paradigma Akuntansi, 2022)
The purpose of this study is to empirically examine the influence of CAR, NIM, LDR, and BOPO, towards ROA on banking companies listed in Indonesia Stock Exchange from the period of 2017–2019. Sample was selected using purposive sampling method and the valid data was 68 data. Data processing techniques using multiple regression analysis by Eviews version 10 and helped by Microsoft Excel 2013. The results of this study indicate that CAR and LDR has positive no significant influence towards ROA, NIM has positive significant influence towards ROA, and BOPO Ratio has negative significant influence towards ROA. The implication of this study is the need to increase NIM and decrease BOPO that will increase ROA which will bring a good signal for investors.